Respuesta :
Yes, that is correct due to the distributive property. It states that you can distribute a number to another number.
for example: a(b + c) = ab + ac
in this case, you are distributing the -1 into the 2x + 10
-1(2x + 10)
(-1) * (2x) + (-1) * (10)
(-2x) + (-10)
-2x - 10
for example: a(b + c) = ab + ac
in this case, you are distributing the -1 into the 2x + 10
-1(2x + 10)
(-1) * (2x) + (-1) * (10)
(-2x) + (-10)
-2x - 10
yes you are correct. this is due to the distributive property of multiplication.
[tex]a(b+c)=ab+ac[/tex]
so [tex]-1(2x+10)=-1(2x)+(-1)(10)[/tex]
[tex]=-2x-10[/tex]
[tex]a(b+c)=ab+ac[/tex]
so [tex]-1(2x+10)=-1(2x)+(-1)(10)[/tex]
[tex]=-2x-10[/tex]